DEVELOPMENT OF SOCIAL ATTITUDE ASSESSMENT INSTRUMENTS BASED ON GOOGLE FORM IN 2013 CURRICULUM AT SDN 050591 PADANG CERMIN, LANGKAT REGENCY - Dwi Afrilia; Daulat Saragi; Yusnadi (SENSEI RESEARCH CENTER, 2022)
This study aims to produce a valid and effective google form-based social attitude assessment instrument used in the 2013 curriculum. This research was conducted at the State Elementary School 050591 Padang Cermin. The population in this study were high-class students at SD Negeri 050591 Padang Cermin Langkat Regency and the sample in this study were classroom teachers using a google form-based social attitude assessment instrument. This research method is a development research proposed by Rusilowati, namely: (1) instrument specifications, (2) writing instruments, (3) determining the scale of the instrument, (4) scoring system, (5) instrument review, (6) assembling the instrument, (7) instrument testing, (8) analysis of test results, (9) instrument improvement, (10) assessment implementation, and (11) instrument development. The results showed (1) Based on the results of the validity of the instrument experts 94.44%, design experts 85.42%, and linguists 94, 23%. From the results of the validation of the developed instrument, the instrument is included in the very good criteria and is declared valid and feasible to use; and (2) the google form-based social attitude assessment instrument is categorized as practical because the instruments resulting from student responses from small-scale trials and large-scale trials have increased.